The Effect of Management Compensation and Debt Requirements on Earnings Management Concerning The Impairment of Assets - Abrigo, Lloyd Kevin Co; Ferrer, Rodiel C. (Journal of Accounting and Investment, 2016)
This study determines the relationship between the impairment decision, as well as its magnitude, and two earnings management motivations, namely increasing management compensation, and meeting debt requirements. The computation of value in use in the impairment loss is subject to managementâ€™s estimate of future cash flows and choice of discount rate, which tolerates earnings management. Certain indicators and financial ratios were used to depict the effect of the two motives on impairment. In addition to this, the effect of firm size on impairment was also analyzed. The data were obtained from the OSIRIS database and the SEC form 17-A of the respective companies, as well as from telephone interviews and surveys. Probit regression was used to analyze the effect of the different motives to the impairment decision while multiple linear regression was used for the impairment magnitude. The findings show that publicly listed companies in the Philippines are engaging in â€œincome smoothingâ€ and â€œbig bathâ€ accounting with the use of impairment. Results also indicate that most â€œbig bathâ€ happens during periods where changes in the companyâ€™s executive officers occur. Lastly, there is also evidence that financially strong companies are deferring their impairment recognition to obtain a lower cost of financing.